Influence of CuO/MgO ratio on the gene expression, cytocompatibilty, and antibacterial/anticancerous/analgesic drug loading kinetics for (15‐x) CuO‐xMgO‐10P2O5‐60SiO2‐10CaO‐5ZnO (2.5 ≤ x ≤ 12.5) mesoporous bioactive glasses. Issue 8 (17th April 2018) - Bains, Rupinderjeet; Sharma, Piyush; Mir, Rameez Ahmad; Jeet, Suninder; Kaur, Gurbinder; Pandey, Om Prakash
Abstract: In the present study, novel mesoporous bioactive glasses (MBGs) (15‐x)CuO‐xMgO‐10P2 O5 ‐60SiO2 ‐10CaO‐5ZnO (2.5 ≤ x ≤ 12.5, varying in steps of 2) are synthesized using the sol‐gel technique. The structural phases of the glasses/glass ceramics were studied by XRD. The pH variation and simulated body fluids (SBF) studies demonstrated the in‐vitro bioactivity of all the MBGs. MBGs possess surface area variation between 98.22 and 442.41 cm 2 /g. The pore size of MBGs lies in the range of 5.8–8.8 nm. The cytotoxicity assays were conducted for MG63 human osteosarcoma cell line depicting non‐toxic behavior of all MBGs at 7.8125 μg/ml. In addition to this, the effect of the magnesium on the gene expression was also investigated using reverse transcription–polymerase chain reaction (RT‐qPCR). The MBGs were loaded with the antibacterial (vancomycin/amoxicillin), anticancerous (doxorubicin), and analgesic (Iburofen) drugs. Ibuprofen and amoxicillin drugs were almost fully loaded in all the MBGs, whereas doxorubicin and vancomycin drugs illustrated variation in loading with decreasing copper content. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 2116‐2130, 2018.